Production and Composition of Purse Seine Catches on FADs in Tobelo Waters - Yani Barakati; Aisyah Bafagih; Syahnul S. Titaheluw; Ruslan A. Daeng (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The research was conducted over a period of one month in the waters of Tobelo with the aim of identifying fish species caught using purse seine fishing gear and determining the variation in species numbers and total catch during the research in the waters of Tobelo, North Halmahera Regency. This study is an experimental fishing study with data analysis in the form of identification and quantitative descriptive statistics to explain the composition of purse seine catch based on data using histograms and tables. The results of the study showed that the pelagic fish species caught were skipjack tuna (Euthynnus affinis), Spanish mackerel (Elagatis bipinnulata), yellowfin tuna (Katsuwonus pelamis), mackerel (Decapterus spp.), and mackerel (Rastrelliger spp.), where mackerel and mackerel were the dominant pelagic fish species in the catch during the study. This was due to various factors, including migratory patterns that tend to form schools and abundant food sources.